472 Employer accommodations and productivity loss for long-term sick-listed workers before, during and after sick-leave. (24th April 2018) - Ekberg, Kerstin; Bernfort, Lars; Persson, Jan
Abstract : Introduction: The study aimed to explore which interventions were performed by employers for sick-listed workers, employer costs for these measures, and if sickness presenteeism before and after the sick-leave period created costs for the employer. Methods: A web-questionnaire was sent to 393 supervisors of sick-listed workers (>30 days) due to common mental disorders or musculoskeletal disorders randomly drawn from the national AFA Insurance registers. The questionnaire comprised questions about work tasks, accommodations and interventions to facilitate RTW, and estimated costs for these measures. Presenteeism was measured by questions on duration and degree of reduced work performance before and after sick-leave. Lost productivity during sick-leave was based on a question regarding performance of replacements. Accommodations were grouped using factor analysis. Statistical analyses were performed with multiple logistic regression analysis. Results: Response rate was 50% (n=198). The most common interventions by supervisors were contacts with other stakeholders, most often HR, occupational health care, and/or Social Insurance Office. Changed work tasks were the most common interventions at the workplace and psychotherapy was the most common individual intervention. Supervisors had difficulties in estimating costs for these interventions. In multiple logistic regression analysis contacts with other stakeholders increased time to RTW (OR=0.68, p<0.02), changed or increased staffing reduced time to RTW (OR=1.43, p<0.05), as did ergonomic interventions (OR=1.74, p<0.004), and work task adjustments (OR=1.41, p<0.07). Demographic factors were not associated with time until RTW. Employer costs for productivity loss before, during and after sick-leave were on average 10 000 EUR. Discussion: Workplace interventions reduce time to RTW, while supervisory contacts with other stakeholders are associated with prolonged sick-leave. Costs due to presenteeism before and after RTW highlights the need for increased attention to preventive measures at the workplace before sick-leave, as well as for support during re-integration after RTW, to reduce productivity loss.